Sexuality and sex therapy : a comprehensive Christian appraisal - Yarhouse, Mark A., 1968-; Christian Association for Psychological Studies (Downers Grove, Illinois : IVP, an imprint of InterVarsity Press, 2014)
The field of human sexuality is one of ever-increasing complexity, particularly for Christian therapists and psychologists seeking to be faithful to Scripture, informed by science and sensitive to culture. In Sexuality and Sex Therapy, Mark Yarhouse and Erica Tan offer a survey and appraisal of this field from a Christian perspective, which grounds sex therapy in the biblical affirmation of physicality and the redemptive purposes of human life. Integrating the latest research within a Christian worldview, the authors explore sexual dysfunctions as well as various clinical issues and treatments. --from back cover.
Part I. Foundational considerations -- Sexuality in theological perspective -- Sexuality in sociocultural perspective -- Sexuality in biological perspective -- Sexuality in clinical perspective -- Part II. Sexual dysfunctions -- Sexual interest and arousal disorders -- Female orgasmic disorder -- Sexual pain disorders -- Erectile disorder -- Rapid and delayed ejaculation -- Part III. Additional clinical presentations -- The paraphilias -- Sexual addiction -- Sexual identity conflicts -- Gender dysphoria -- Part IV. Future directions -- Christianity and sex therapy.
Includes bibliographical references and index.
Keywords: Sex -- Religious aspects -- Christianity; Sex therapy; Sex -- Religious aspects -- Christianity; Sex therapy